m = 70 kg, L = 4.0 m,

(a) at the beginning of his motion T=0

b) h = 1.5 m

\(\displaystyle{m}{g}{L}={m}{g}{h}+{m}\frac{{v}^{{2}}}{{2}}\)

so \(\displaystyle{m}{v}^{{2}}={2}{m}{g{{\left({L}-{h}\right)}}}\)

\(\displaystyle{T}-{m}{g}{\cos{\theta}}={\frac{{{m}{v}^{{2}}}}{{{L}}}}\) where \(\displaystyle{\cos{\theta}}={\frac{{{L}-{h}}}{{{L}}}}\)

\(\displaystyle\therefore{T}={m}{g}{\frac{{{L}-{h}}}{{{L}}}}+{2}{m}{g}{\frac{{{L}-{h}}}{{{L}}}}={3}{m}{g}{\frac{{{1}-{h}}}{{{L}}}}={1286}\ {N}\)

c) let h=0 in \(\displaystyle{T}={3}{m}{g}{\frac{{{1}-{h}}}{{{L}}}}\)

So T=3mg=2058 N

(a) at the beginning of his motion T=0

b) h = 1.5 m

\(\displaystyle{m}{g}{L}={m}{g}{h}+{m}\frac{{v}^{{2}}}{{2}}\)

so \(\displaystyle{m}{v}^{{2}}={2}{m}{g{{\left({L}-{h}\right)}}}\)

\(\displaystyle{T}-{m}{g}{\cos{\theta}}={\frac{{{m}{v}^{{2}}}}{{{L}}}}\) where \(\displaystyle{\cos{\theta}}={\frac{{{L}-{h}}}{{{L}}}}\)

\(\displaystyle\therefore{T}={m}{g}{\frac{{{L}-{h}}}{{{L}}}}+{2}{m}{g}{\frac{{{L}-{h}}}{{{L}}}}={3}{m}{g}{\frac{{{1}-{h}}}{{{L}}}}={1286}\ {N}\)

c) let h=0 in \(\displaystyle{T}={3}{m}{g}{\frac{{{1}-{h}}}{{{L}}}}\)

So T=3mg=2058 N